Monte Carlo study of the micelles constructed by ABCA tetrablock copolymers and their formation in A-selective solvents. Issue 105 (13th October 2015) - Ma, Jiani; Cui, Jie; Han, Yuanyuan; Jiang, Wei; Sun, Yingchun
Abstract : Micelles with hamburger-type and Janus-type solvophobic parts, asymmetric vesicles with multicompartment outer surface formed by ABCA tetrablock copolymers in A-selective solvent. Abstract : The phase behavior of the ABCA tetrablock copolymers in A-selective solvents is investigated using Lattice Monte Carlo simulation. The main focus is the effects of the solvophobic interactions of blocks B and C ( ε BS and ε CS ) on the micelle morphologies. Three kinds of ABCA tetrablock copolymers, i.e., A2 B6 C6 A2, A2 B7 C5 A2 and A2 B8 C4 A2 tetrablock copolymers, are considered. Phase diagrams of these three tetrablock copolymers as a function of ε CS and the solvophobic interaction difference between blocks B and C (which is measured by r = ε BS / ε CS ) are given and discussed. It is found that r and ε CS can both affect the specific surface area of micelles and lead to the morphological changes of ABCA tetrablock copolymer micelles. In addition, r can change the solvophobic chain conformation and hence affect the micro-structures of the solvophobic parts of the micelles. For A2 B7 C5 A2 and A2 B8 C4 A2 tetrablock copolymers, several novel micelle morphologies, such as the bended Janus ribbon and lamella, short Janus tube, and bowl-shaped semivesicle, are obtained. Interestingly, it is found that in the phase diagrams of A2 B7 C5 A2 and A2 B8 C4 A2 tetrablock copolymers, the micelle type with Janus-like solvophobic parts is the majority micelle type, which mainly results from the solvophobic interaction balance between blocks B and C. Moreover, the formation pathways for these novel Janus-type micelles are given and discussed.